Community Participation in Natural Disaster Mitigation Based on Local Wisdom "Adat Cao Mukak Imbo" North Bengkulu Regency of Bengkulu Province Indonesia - Soni, Aprianto (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2021)
Environmental damage has a direct impact on human life judging by environmental problems that are increasingly rampant. This damage is caused by human activities that are not environmentally friendly that always occur so that environmental damage does not occur continuously for human life in the future need better recovery. Community participation can be given in the form of thoughts/ideas, materials, energy, and skills to help the success of disaster management programs. The method used in this research is the ethnographic method about the Rejang tribe community as the center of competency cultivation including qualitative research type. Local wisdom of Cao Mukak Imbo Custom in Rejang tribal communities is very rich in forms of local wisdom can be in the form of values, norms, beliefs, and special rules. The form of local wisdom Cao Mukak Imbo Custom is very instrumental in disaster mitigation as for the prohibition contained in the local wisdom is the rule of working on land steep areas or around waterfalls if we review in fact because these areas are water catchment areas and when cultivated and planted plants such as palawija can trigger landslides or floods. Preserving the culture we have will encourage the skills and knowledge possessed by local communities. Local wisdom a noble value prevailing in the community's life system to protect and manage the environment wisely and wisely so that the environment is maintained sustainably.